2018
DOI: 10.1016/j.jclepro.2017.12.088
|View full text |Cite
|
Sign up to set email alerts
|

Influence of technical failures on the performance of an optimized community-size solar heating system in Nordic conditions

Abstract: There is a substantial need to accelerate the advancement and implementation of clean energy technologies in order to solve the challenges of the energy crisis and climate change. Solar heating technology is a feasible solution among clean energy technologies. In real conditions such complex systems often suffer from different kinds of technical failures and deviations reducing the system performance. This paper focuses on the challenges of a solar district heating system at high latitudes, proposes an optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Nevertheless, under realistic operation setup, the monitoring data indicated that a solar fraction between 21% and 33% is attainable [8]. Higher solar fraction value has never been obtained as a result of many problems such as higher heating demand in comparison to expectation, increased thermal losses in the seasonal storage, and reduced heat exchanger and solar collector efficiencies [7]. Similar problem has been detected in other SDHS installed in Rockstock and Neckarsulm [9].…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Nevertheless, under realistic operation setup, the monitoring data indicated that a solar fraction between 21% and 33% is attainable [8]. Higher solar fraction value has never been obtained as a result of many problems such as higher heating demand in comparison to expectation, increased thermal losses in the seasonal storage, and reduced heat exchanger and solar collector efficiencies [7]. Similar problem has been detected in other SDHS installed in Rockstock and Neckarsulm [9].…”
Section: Introductionmentioning
confidence: 67%
“…Unsurprisingly, performance has not been at par given that the theoretical models used in pre-studies discuss performance under ideal conditions. Many operational challenges have to do with the wrong application of various technologies [7].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless, simulated studies are sure to be overly optimistic as real systems always suffer from unexpected problems, such as component failures, less than ideal efficiencies, uncontrolled ground water flows and different than expected environmental conditions. Such technical problems and non-ideal behaviour have been studied in (Rehman et al, 2018). (Nussbicker et al, 2004;Schmidt and Mangold, 2006 with the Finnish case in this study.…”
Section: Comparison To Other Studiesmentioning
confidence: 97%
“…Moreover, various combinations of storages, renewable energy generation and electric vehicles are compared, both technically and economically for cold conditions. The renewable district heating system, seasonal storages and buildings have been simulated and optimized in earlier studies [48,49]. In the current paper the focus is on the optimized integration of the renewable electrical generation system, electrical storages, grid connection and electric vehicles in the community and the comparison between various combinations (technically and economically).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…The research aim and objective of this paper is to facilitate and propose the rollout of the community-scale renewable electricity systems in Finland and also to widen the optimization study made in the previous work [48,49], where community-scale renewable district heating system is only studied. The electrical, heating systems and buildings in the community are integrated, optimized and studied together in the present paper.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%